Beryllium inhibits apoptosis via mitochondria in beryllium-induced lung disease in the rat. (21st April 2019) - Liu, Zhihong; Wang, Kai; Yan, Qing; Wang, Hejing; Zhang, Na; Gong, Aihong; Guo, Xiong
Abstract: Objective: We aimed to determine whether beryllium toxicity was associated with mitochondria apoptosis pathway in SD rats. Methods: Thirty-two SD rats were given an intratracheal instillation dose of 10 g/l beryllium oxide (0.5 ml per rat). Additional 32 rats were given an intratracheal instillation dose of 0.9% normal saline (0.5 ml per rat). The percentage of apoptosis, mitochondrial membrane potential, the expression level of apoptosis related genes and proteins, including bcl2, Bax and Caspase-3 were detected. Results: The average of percentage of apoptosis, the expression of caspase-3, bax, and cytochrome c were decreased significantly in lung tissues from rats exposed to beryllium oxide compared to normal controls. The expression of bcl2 and ADP were increased significantly at 80 d after exposure. Conclusions: We conclude that inhibition of apoptosis by beryllium oxide involves mitochondrial apoptosis pathway in rat model of beryllium oxide-induced pulmonary disease.